LEADERSHIP INFLUENCE AND SATISFACTION WORK TO OFFICER PERFORMANCE OF SOCIAL ON DUTY AND LABOUR OF PASAMAN REGENCY - Hermawan, Bubung Mukhtar (jurnal ekonomi, 2008)
This research target is to prove the leadership influence and satisfaction work to officer performance of social on duty anf labour of Pasaman regency. Method used by with the double linear regression by object research is entire/ all officer of social on duty and labour of Pasaman regency as much 40 people. Result of research conclude thatleadership and satisfaction work by parsial have an affect on the significant to social officer performance on duty and labour of Pasaman regency. And so do by second together variable namely laedership and satisfaction work to have an effect on the significant to social officer performance on duty and labour of Pasaman regency. Result of this research give the public information and picture for the mangement that leadership and satisfaction work to have the important meaning in improving officer performance. On that account mangement of social on duty and labour of Pasaman regency so that to be more paying attention to and improving leadership and satisfaction work by improving head ability, improving thinking ability, and need the existense of attention to officer of so that they get the satisfaction in working.